Autoimmunity risk- and protection-associated IL7RA genetic variants differentially affect soluble and membrane IL-7Rα expression. (February 2019) - Lundtoft, Christian; Seyfarth, Julia; Oberstrass, Sonja; Rosenbauer, Joachim; Baechle, Christina; Roden, Michael; Holl, Reinhard W.; Mayatepek, Ertan; Kummer, Sebastian; Meissner, Thomas; Jacobsen, Marc
Abstract: Interleukin-7 receptor α-chain ( IL7RA ) haplotypes are associated with susceptibility to autoimmune diseases including type 1 diabetes (T1D). Previous studies found lower soluble IL-7Rα (sIL-7Rα) serum levels of the protection-associated IL7RA haplotype assumed to reduce IL-7 availability for self-reactive T cells. Also, a risk-associated IL7RA haplotype is accompanied by lower sIL-7Rα serum concentrations but no underlying mechanisms have been described and the causative polymorphism remains unknown. Here, we characterized functional implications of the nonsynonymous rs1494558 (Thr66Ile), which tags the protection-associated IL7RA haplotype, in HEK293T cells and serum samples of T1D patients with different haplotype carriers. Influence of risk- and protection-associated haplotypes on IL-7Rα was analyzed. The risk-associated Ile66 variant affected gel mobility and impaired secretion of the sIL-7Rα as well as expression of the membrane-associated (m)IL-7Rα in HEK293T cells. Serum sIL-7Rα analyses confirmed differential gel mobility of the Ile66 variant and found decreased sIL-7Rα serum levels of T1D patients carrying the Ile66-tagged haplotype. Differences in glycosylation were not causative for differential mobility but enhanced the effects on impaired secretion. Comparison of protection- and risk-associated haplotypes in a cell line-based in vitro model identified dominant effects of the protective haplotype tagged by rs6897932 (Ile244) on mIL-7Rα expression, whereas the risk haplotype mainly affected the sIL-7Rα. This study identified novel functional effects of the Ile66 IL7RA variant and characterized features of autoimmunity risk- and protection-associated haplotypes. The findings add to our understanding of how these haplotypes regulate sIL-7Rα and mIL-7Rα expression in T cells causing differential susceptibility to autoimmune diseases. Graphical abstract: Highlights: The autoimmunity risk-associated IL7RA Ile66 variant impairs secretion of sIL-7Rα. Type 1 diabetes patients with Ile66 have lower soluble IL-7Rα serum levels. Conformational changes induced by Ile66 were glycosylation independent. Risk- and protection- (Ile244) associated haplotypes affect sIL-7Rα secretion. Membrane IL-7Rα expression was only increased for the IL7RA Ile244 allele.